Pendekatan Inverse Action Research dalam Pengadaan Lahan Tanah di MWC NU Sruweng - Agus Salim Chamidi; Bahrun Ali Murtopo; Dewi Oktaviana (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
collaboration between lecturers and KKN IAINU Kebumen students in 2021. The research location is at the Nahdlatul Ulama Representative Council (MWCNU) Sruweng Kebumen. The purpose of the research is to find out the process of social transformation that occurs at MWCNU Sruweng by examining the background and goals behind the success of MWCNU Sruweng holding land owned by MWCNU Sruweng, as well as knowing the concepts and values ​​behind it. The research is qualitative with an inverse action research approach model. Research informants were a number of MWCNU Sruweng administrators who were involved in land acquisition. The research was conducted in August-September 2021. The results of the research are: (a) the research model succeeded in exploring the background of the problem and the objectives of land acquisition, (b) the main concept of land acquisition for MWCNU Sruweng as a physical facility, which in the future will be able to build buildings MWCNU Sruweng for the development of the religious life of NU residents in the Sruweng area, in order to achieve community welfare both spiritually and materially, (c) there are concepts and noble values ​​based on culture and religion behind land acquisition. Suggestions, that the research model and values ​​that have been investigated are appropriate to be used for the purposes of looking at society's present, past, and future. Keywords: inverse action research, MWC NU Sruweng, land acquisition.